An anatomy of waste generation flows in construction projects using passive bigger data. (1st April 2020) - Xu, Jinying; Lu, Weisheng; Ye, Meng; Webster, Chris; Xue, Fan
Highlights: This paper portrays the waste generation flow (WGF) of 132 construction projects. Different WGFs follow different S-curves, but are far from steady streams. The peaks of waste generation rates differ across projects. New building projects generate waste faster than demolition and foundation projects. Abstract: Understanding waste generation flow is vital to any evidence-based effort by policy-makers and practitioners to successfully manage construction project waste. Previous research has found that accumulative waste generation in construction projects follows an S-curve, but improving our understanding of waste generation requires its investigation at a higher level of granularity. Such efforts, however, are often constrained by lack of quality "bigger" data, i.e. data that is bigger than normal small data. This research aims to provide an anatomy of waste generation flow in building projects by making use of a large set of data on waste generation in 19 demolition, 59 foundation, and 54 new building projects undertaken in Hong Kong between 2011 and 2019. We know that waste is generated in far from a steady stream as it is always impacted by contingent factors. However, we do find that peaks of waste generation in foundation projects appear when project duration is at 50–85%, and in new building projects at 40–70% of total project time. Our research provides useful information for waste managers in developing their waste management plans, arranging waste hauling logistics, and benchmarking waste management performance.